Kepemimpinan Pendidikan Nabi Yusuf - Arifin, Muhammad Zainul (Institut Agama Islam Negeri (IAIN) Tulungagung, 2016)
The characteristics of the Prophet Yusuf leadership among other things: 1) A leader of professional, honest and provide exemplary; 2) Have the ability and high intelligence and wisdom; 3) The leader of a fair; 4) Thorough leader and mandate; 5) Leaders are consistent; 6) Ability to work hard to create a climate of tolerance; 7) Be confident (optimistic). The concept of leadership is understandable based on the story of Prophet Yusuf, a proactive leader, and have a clear objective of improving the welfare of its people. Yusuf is a multi social leader, knows no ethnic differences, so keep nurturing it all.Keywords: Educational, Leadership of The Prophet Yusuf.